2021
DOI: 10.1128/jb.00415-21
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Dihydroxyacid Dehydratase Induces Auxotrophy in Bacillus anthracis

Abstract: Anthrax disease is caused by infection with the bacteria Bacillus anthracis which, if left untreated, can result in fatal bacteremia and toxemia. Current treatment for infection requires prolonged administration of antibiotics. Despite this, inhalational and gastrointestinal anthrax still result in lethal disease. By identifying key metabolic steps that B. anthracis uses to grow in host-like environments, new targets for antibacterial strategies can be identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The deletion of BCAA biosynthesis genes in other bacteria harboring apparent BCAA transporter genes, including L. monocytogenes and S. pneumoniae , also results in reduced virulence ( 20 , 63 ). We note that while the manuscript was in review, Jelinski et al reported work indicating that an ilvD -null mutant of B. anthracis strain 34F2 was not attenuated in a murine model using intranasal infection with spores ( 64 ). The bacterial strain and infection models differed from those employed in our study, and the basis for this conflicting result will be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of BCAA biosynthesis genes in other bacteria harboring apparent BCAA transporter genes, including L. monocytogenes and S. pneumoniae , also results in reduced virulence ( 20 , 63 ). We note that while the manuscript was in review, Jelinski et al reported work indicating that an ilvD -null mutant of B. anthracis strain 34F2 was not attenuated in a murine model using intranasal infection with spores ( 64 ). The bacterial strain and infection models differed from those employed in our study, and the basis for this conflicting result will be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The spores are resilient to certain chemicals and elements, and they can survive in the soil for almost 50 years. The bacteria return to the disease-causing vegetative stage when the spores gain entry in an animal, generally by feeding infected grass or by respiration (Jelinski et al 2021).…”
Section: Etiopathologymentioning
confidence: 99%